Feasibility and efficacy of preoperative chemoradiotherapy in patients with locally advanced gastric cancer - Yong-Heng Li; Zhong-Wu Li; Shi-Jie Li; Lei Tang; Shuang- Xi Li; Zhao-De Bu; Xiao-Fan Li; Zi-Yu Li; Jia-Fu Ji (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: Investigate the feasibility and efficacy of neoadjuvant chemoradiotherapy for locally advanced gastric cancer. Methods: Intensity-modulated radiotherapy (IMRT), with 50/45 Gy in 25 fractions. The concurrent chemotherapy regimens included oral TS-1 plus oxaliplatin 40 mg/m2 intravenously weekly (10 patients) or TS-1 alone (120 mg/day, 25 patients). Surgical resection was performed within 6~8 weeks after the last day of radiotherapy. Results:No grade 4 toxicity recorded. The incidence of grade 3 toxicity is 11.4%: thrombocytopenia (5.7%), neutropenia (2.9%) and radiation esophagitis (2.9%). Pathological complete response 8.6% (3/35).Surgery-related complications consisted of anastomotic leakage in 2 patients (7.1%), infection in 3 (10.7%) and hemorrhage in 2 (7.1%). No postoperative mortality was recorded. The 1-year and 2-year overall survival (OS) rates were 88.3% and 59.6%respectively. Conclusion: In this study, neoadjuvant chemoradiotherapy showed an acceptable toxicity and promising efficacy in patients with locally advanced gastric cancer.